The Nature of Option Interactions and the Valuation of Investments with Multiple Real Options - Trigeorgis, Lenos (Journal of Financial and Quantitative Analysis, 1993)
prior permission, you may not download an entire issue of a journal or multiple copies of articles, and you may use content in the JSTOR archive only for your personal, non-commercial use. Please contact the publisher regarding any further use of this work. Publisher contact information may be obtained at